Perception of Indonesian Students on the Importance of Anti-Corruption Education - Kusen, Kusen (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2022)
The purpose of this study was to determine student perceptions of the Tarbiyah Faculty of IAIN Curup about the importance of anti-corruption education in Indonesia. This research is a type of quantitative descriptive research. The population taken in this study were all students at IAIN Curup. The sampling technique used is probability sampling with the number of data samples, namely 118 students from 7 study programs from the Tarbiyah Faculty. Collecting data using a questionnaire. The instrument used in this study was a questionnaire on the perception of students from Tarbiyah IAIN that they were bad at the importance of anti-corruption education in Indonesia. This research was conducted at IAIN Curup, Rejang Lebong Regency, Bengkulu Province in May 2022. The questionnaire asked students' opinions about the importance of anti-corruption education in Indonesia. In this study, the questionnaire was prepared using a four-point scale, with Strongly Agree, Agree, Disagree, and Strongly Disagree. The results of this study indicate that students of the Tarbiyah Faculty of IAIN Curup consider the importance of anti-corruption education in Indonesia. Anti-corruption education is important to shape anti-corruption characteristics for the younger generation by showing the phenomenon of corruption to the consequences of corruption itself.